The role of temperature and adsorbate on negative gas adsorption transitions of the mesoporous metal–organic framework DUT-49. (29th October 2020) - Krause, Simon; Evans, Jack D.; Bon, Volodymyr; Senkovska, Irena; Coudert, François-Xavier; Többens, Daniel M.; Wallacher, Dirk; Grimm, Nico; Kaskel, Stefan
Abstract : Adsorption-induced contraction and negative gas adsorption in the mesoporous metal–organic framework DUT-49 for different gases and temperatures. Abstract : Unusual adsorption phenomena, such as breathing and negative gas adsorption (NGA), are rare and challenge our thermodynamic understanding of adsorption in deformable porous solids. In particular, NGA appears to break the rules of thermodynamics in these materials by exhibiting a spontaneous release of gas accompanying an increase in pressure. This anomaly relies on long-lived metastable states. A fundamental understanding of this process is desperately required for the discovery of new materials with this exotic property. Interestingly, NGA was initially observed upon adsorption of methane at relatively low temperature, close to the respective standard boiling point of the adsorptive, and no NGA was observed at elevated temperatures. In this contribution, we present an extensive investigation of adsorption of an array of gases at various temperatures on DUT-49, a material which features an NGA transition. Experiments, featuring a wide range of gases and vapors at temperatures ranging from 21–308 K, were used to identify for each guest a critical temperature range in which NGA can be detected. The experimental results were complemented by molecular simulations that help to rationalize the absence of NGA at elevated temperatures, and the non-monotonic behavior present upon temperature decrease. Furthermore, this in-depth analysis highlights the crucial thermodynamic and kinetic conditions for NGA, which are unique to each guest and potentially other solids with similar effects. We expect this exploration to provide detailed guidelines for experimentally discovering NGA and related "rule breaking" phenomena in novel and already known materials, and provide the conditions required for the application of this effect, for example as pressure amplifying materials.